Perinatal cortical infarction within middle cerebral artery trunks. Issue 1 (1st January 2000) - Govaert, Paul; Matthys, Erika; Zecic, Alexandra; Roelens, Filip; Oostra, Ann; Vanzieleghem, Bart
Abstract : AIM: To define neonatal pial middle cerebral artery infarction. METHODS: A retrospective study was made of neonates in whom focal arterial infarction had been detected ultrasonographically. A detailed study was made of cortical middle cerebral artery infarction subtypes. RESULTS: Forty infarctions, with the exception of those in a posterior cerebral artery, were detected ultrasonographically over a period of 10 years. Most were confirmed by computed tomography or magnetic resonance imaging. Factor V Leiden heterozygosity was documented in three. The onset was probably antepartum in three, and associated with fetal distress before labour in one. There were 19 cases of cortical middle cerebral artery stroke. The truncal type (n=13) was more common than complete (n = 5) middle cerebral artery infarction. Of six infarcts in the anterior trunk, four were in term infants and five affected the right hemisphere. Clinical seizures were part of the anterior truncal presentation in three. One of these infants, with involvement of the primary motor area, developed a severe motor hemisyndrome. The Bayley Mental Developmental Index was above 80 in all of three infants tested with anterior truncal infarction. Of seven patients with posterior truncal infarction, six were at or near term. Six of these lesions were left sided. Clinical seizures were observed in three. A mild motor hemisyndrome developed in at least three of these infants due to involvement of parieto-temporal non-primary cortex. CONCLUSIONS: Inability to differentiate between truncal and complete middle cerebral artery stroke is one of the explanations for the reported different outcomes. Severe motor hemisyndrome can be predicted from neonatal ultrasonography on the basis of primary motor cortex involvement. Clinical seizures were recognised in less than half of the patients with truncal infarction; left sided presentation was present in the posterior, but not the anterior truncal type of infarction. Asphyxia is a rare cause of focal arterial infarction.